2018
DOI: 10.1039/c8dt02099j
|View full text |Cite
|
Sign up to set email alerts
|

A cationic organoiridium(iii) complex-based AIEgen for selective light-up detection of rRNA and nucleolar staining

Abstract: A green emissive cationic organoiridium(iii) complex, 2[PF6], with a benzimidazole-substituted 1,2,3-triazole-pyridine (BiPT) ligand has been synthesized for target-specific cellular imaging and selective detection of ribosomal RNA (rRNA) over other competitive biomolecules in aqueous buffer solution at physiological pH. Complex 2 shows aggregation-induced emission enhancement (AIEE) properties and forms nano-aggregates in the presence of poor solvents. DFT and TD-DFT-based quantum mechanical calculations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…The ESI-MS of the Ru-1 and NaOCl mixture shows a clear peak at m / z = 770.13, corresponding to [C 39 H 26 ­N 9 ORuS] + , which indicates oxidation in Ru-1 (Figure S21). While Ru-1 may undergo HOCl/ClO – mediated S-oxidation of benzothiazole to sulfoxide or sulfonate, the possibility of oxidation in 1,2,3-triazole is considered since our previous work on Ru­(II) based probes attests that the reactive C-H of 1,2,3-triazole is responsible for the PL enhancement …”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The ESI-MS of the Ru-1 and NaOCl mixture shows a clear peak at m / z = 770.13, corresponding to [C 39 H 26 ­N 9 ORuS] + , which indicates oxidation in Ru-1 (Figure S21). While Ru-1 may undergo HOCl/ClO – mediated S-oxidation of benzothiazole to sulfoxide or sulfonate, the possibility of oxidation in 1,2,3-triazole is considered since our previous work on Ru­(II) based probes attests that the reactive C-H of 1,2,3-triazole is responsible for the PL enhancement …”
Section: Resultssupporting
confidence: 80%
“…Probe Ru-1 , readily prepared from BtPT and cis -[Ru­(phen) 2 ]­Cl 2 (Scheme ), was characterized by 1D ( 1 H and 13 C) and 2D (COSY, HSQC, and HMBC) NMR, ESI-MS (Figures S6–S11), and single-crystal X-ray diffraction (Figure and Tables S2 and S3). Like previously reported Ru­(II) based probes, , here, the Ru­(II) center adopts a distorted octahedral geometry with the trans angles ranging from 170.69(18)° to 172.54(17)°. Additionally, complex Ru-2 of the methyl substituted pyridyl triazole ligand was synthesized to support the mechanistic details of the probe analyte reaction (Scheme , inset).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5c shows that the proton signals Ha, Hb, Hc and Hd on the pyridine ring moved towards high magnetic fields after RNA addition, with the signal intensity decreasing gradually. These data indicated that the location of hydrogen atoms may be the binding sites of RNA 42. Molecular-docking simulation showed that the interaction between the DZ1 molecule and RNA was a charge–charge interaction because the RNA surface was anionic and DZ1 possessed a positive charge (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Upon aggregation, the RIM process blocks the nonradiative decay from the excited state and populates the radiative decay channels. In addition to RIM, several processes such as planarization, J-aggregate formation, internal charge transfer (ICT), and E – Z isomerization also contribute to the AIE effect. , Extensive applications of AIE-active luminogens such as organic light-emitting diodes, bio/chemosensing, cell imaging, drug delivery, etc., have attracted the attention of numerous scientists. , Scientists have expanded this exciting AIE field mostly by developing organic-based AIEgens, together with a few metal complexes. , However, among metal complex-based AIEgens, Ru­(II) complex-based AIE materials are very rare. , …”
Section: Introductionmentioning
confidence: 99%